MID CRETACEOUS SUBSURFACE CARBONATE DEPOSIT AND RESERVOIR DEVELOPMENT OF THE MFAMOSING LIMESTONE CALABAR FLANK - Selema, S.B.; Ideozu, R.U.; Acra, E.J. (International Journal of Research -GRANTHAALAYAH, 2023)
This research analyzed the reservoir quality of the Mfamosing Limestone with a view to classifying it as a potential reservoir rock within the Calabar Flank. Materials used in this research are processed seismic data acquired around the Calabar flank and well logs of three wells (A, B, C) drilled at different periods within the study area, core as well as mud log data. The procedure used involved prospect identification and mapping, structural and stratigraphic analysis, reservoir quality and classification of the carbonate rock in the study area. The results were analyzed and classified the Mfamosing Limestone using hydrocarbon storage capacity and deliverability potential. Wells A and B was drilled 0.8km apart and well C drilled 4.7km from well B which encountered the Mfamosing Limestone with logs indicating hydrocarbon in Well A which had a shallower sandstone lenses. The sandstone lens in Well A was tested for hydrocarbon and flowed briefly and stopped. Wells B and C were planned and drilled using Well A as reference amongst other parameters to evaluate the hydrocarbon potential of the Mfamosing Limestone. Wells B and C were found completely dry. Two conventional coring runs at depths 10,490ft-10,552.5ft and 10,552.5ft-10,614ft in Well B indicated that the cored intervals are light grey, moderate to very hard, and fossil rich limestone with no direct fluorescence. The core analysis results suggest that limestone is dry and highly indurated with no evidence of physical porosity. This suggest that the Mfamosing Limestone penetrated by all three wells though massive has no hydrocarbon storage capacity and deliverability potential typical of a reservoir rock. This research therefore suggests that the Mid Cretaceous subsurface Mfamosing Limestone is more of a mineral carbonate deposit than a hydrocarbon reservoir.